2021
DOI: 10.2478/euco-2021-0040
|View full text |Cite
|
Sign up to set email alerts
|

Visitors’ Happiness and Loyalty in the Moravian Wine Region

Abstract: Due to the COVID-19 pandemic, tourists’ loyalty is more pronounced than ever. It is therefore inevitable to know what factors can contribute to the higher levels of loyalty among potential visitors. Since none of the previously researched factors are reflecting visitors’ feelings and emotions, and because wine tourism can build long-lasting emotional ties with tourists, this study focuses on Moravian wine region visitors’ happiness within the context of loyalty. Overall, seven loyalty factors influence the hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The review of the research results reported in the articles reveal a variety of constructs that predict destination loyalty as illustrated in Figure 1 . The determinants of destination loyalty found as statistically significant with available effects as Beta coefficients ( Vogt and Johnson, 2016 ) were: satisfaction (β = 0.790) by Papadopoulou et al (2022) ; destination image (β = 0.530) by Zaman et al (2021) ; emotional and functional value (β = 0.477) by Carvache-Franco et al (2022b) ; perceived values (β = 0.382) and emotions (β = 0.434) by Tu et al (2022) ; happiness (β not reported) by Kralikova et al (2021) ; cultural-archaeological and sun-beach motivations (β not reported) by Garcia-Reinoso et al (2021) ; emotional solidarity’s dimensions of feeling welcomed (β = 0.560), emotional closeness (β = 0.240), and sympathetic understanding (β = 0.530) by Woosnam et al (2021) ; tourists’ cultural intelligence (β = 0.166) by Zaman et al (2021) ; destination experiencescape’s dimensions of key attractions (β = 0.250) auxiliary elements (β = 0.380), and atmosphere (β = 0.230) by Lin et al (2022) ; and the overall consumer-based brand equity (CBBE) of the destination (β = 0.590) by Otero-Gomez and Giraldo-Perez (2022) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of the research results reported in the articles reveal a variety of constructs that predict destination loyalty as illustrated in Figure 1 . The determinants of destination loyalty found as statistically significant with available effects as Beta coefficients ( Vogt and Johnson, 2016 ) were: satisfaction (β = 0.790) by Papadopoulou et al (2022) ; destination image (β = 0.530) by Zaman et al (2021) ; emotional and functional value (β = 0.477) by Carvache-Franco et al (2022b) ; perceived values (β = 0.382) and emotions (β = 0.434) by Tu et al (2022) ; happiness (β not reported) by Kralikova et al (2021) ; cultural-archaeological and sun-beach motivations (β not reported) by Garcia-Reinoso et al (2021) ; emotional solidarity’s dimensions of feeling welcomed (β = 0.560), emotional closeness (β = 0.240), and sympathetic understanding (β = 0.530) by Woosnam et al (2021) ; tourists’ cultural intelligence (β = 0.166) by Zaman et al (2021) ; destination experiencescape’s dimensions of key attractions (β = 0.250) auxiliary elements (β = 0.380), and atmosphere (β = 0.230) by Lin et al (2022) ; and the overall consumer-based brand equity (CBBE) of the destination (β = 0.590) by Otero-Gomez and Giraldo-Perez (2022) .…”
Section: Resultsmentioning
confidence: 99%
“…The operationalization of destination loyalty typically included scale items referring to recommendation or positive word-of-mouth (WOM) about the destinations, combined with other revisit intentions items within the same loyalty construct. However, some investigations specified and operationalized tourists’ recommendations or endorsements as additional, separate constructs in their models (e.g., Chebli et al, 2021 ; Kralikova et al, 2021 ; Koç et al, 2022 ; Suhartanto et al, 2022 ; Carvache-Franco et al, 2022a , b ).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, as a thriving niche tourism business, it can provide an effective way to enrich the (regional) tourism product and respond to the visitors' changing interests. It includes the overall goal of strengthening the attractiveness and competitiveness of the destination (Getz, 2000;Mancino and Lo Presti, 2012) but also the tourists' experience, perspective, and loyalty (Králiková et al, 2021;Zamora and Bravo, 2005). At destinations where grapes are grown for wine, visitors can get acquainted with the cultural and historical heritage of the region.…”
Section: Introductionmentioning
confidence: 99%
“…These aspects are further emphasized by the common border with Austria and its cross-border wine-growing region Lower Austria (Niederösterreich), specifically Weinviertel (Flamik, 2020). The Czech Republic is a member of the OIV and has a wine-growing area of 17.9 thousand hectares (in 2020, see Table 1) (Králiková et al, 2021), slightly bigger than Slovenia. Regarding the wine classification, the Czech Republic has the wine of origin (PDO, PGI) just like Slovenia (National Wine Center, 2020).…”
Section: The Case Of the Czech Republicmentioning
confidence: 99%
“…This fact also relates to the number of beds available in the whole country at any one time, given that the Czech Republic offers more than three times as many beds for accommodation compared with Slovenia. Source: AMSP ČR, 2018;CZSO, 2020;GOV.SI, 2021;Králiková et al, 2021;Slovenian Tourist Board, 2020;Statista, 2022;SURS, 2021aSURS, , 2021bTHE Slovenia, 2021;ÚKZÚZ, 2021;World Tourism Organization, 2020. Another similarity between the two wine countries is the way they comprehend wine and wine tourism. Wine is not only consumed.…”
Section: Smart Cities In Generalmentioning
confidence: 99%